PERAN BALAI PEMASYARAKATAN DALAM MENJALANKAN FUNGSI PEMBIMBINGAN TERHADAP KLIEN PEMASYARAKATAN (Studi Pada Balai Pemasyarakatan Kelas 1 Palembang) - Asmawati, Hermi (Journal Evidence Of Law, 2022)
Balai Pemasyarakatan is one part of the correctional system that focuses on the concept of mentoring clients which aims to return convicts who become inmates as good and responsible citizens so that later they can be accepted back into society. This study aims to see how the role of Balai Pemasyarakatan Kelas 1 Palembang in carrying out the guidance function for Correctional Clients. The research method used is normative legal research with a statutory regulation approach. The research results show that Correctional Centers have 4 main functions, namely social research, assistance, guidance, and client supervision both inside and outside the criminal justice process in the framework of social reintegration. However, there are several obstacles that result in supervision by Community Advisors on clients not running optimally, including a large background gap between social counselors and clients, the father's work area is very broad, the dual role of community counselors, limitations of science and technology from clients, negative habits of clients , as well as minimal synergy between law enforcers.